2001
DOI: 10.1034/j.1399-3011.2001.00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformational comparison of µ‐selective endomorphin‐2 with its C‐terminal free acid in DMSO solution, by 1H NMR spectroscopy and molecular modeling calculation

Abstract: In order to make clear the structural role of the C-terminal amide group of endomorphin-2 (EM2, H-Tyr-Pro-Phe-Phe-NH2), an endogenous mu-receptor ligand, in the biological function, the solution conformations of endomorphin-2 and its C-terminal free acid (EM2OH, H-Tyr-Pro-Phe-Phe-OH), studied using two-dimensional 1H NMR measurements and molecular modeling calculations, were compared. Both peptides were in equilibrium between the cis and trans isomers around the Tyr-Pro omega bond in a population ratio of appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 28 publications
2
68
0
Order By: Relevance
“…In contrast, this conformational feature of cis-EM1 was not observed during the MD calculation performed in H 2 O and in vacuo [25]. Similarly as for the cis-isomer of EM1, based on the NMR data, a compact sandwich structure with stacking of the Tyr 1 , Pro 2 , and Phe 3 rings was also detected for cis-EM2 in DMSO and in TFE [27] [29]. Moreover, the results of the RS calculations indicated the presence of compact conformations created by the packing of the side chains of aromatic amino acids around the Pro 2 residue in the case of the cis-isomers of EMs (Fig.…”
Section: Backbone Conformations and Secondarymentioning
confidence: 57%
See 3 more Smart Citations
“…In contrast, this conformational feature of cis-EM1 was not observed during the MD calculation performed in H 2 O and in vacuo [25]. Similarly as for the cis-isomer of EM1, based on the NMR data, a compact sandwich structure with stacking of the Tyr 1 , Pro 2 , and Phe 3 rings was also detected for cis-EM2 in DMSO and in TFE [27] [29]. Moreover, the results of the RS calculations indicated the presence of compact conformations created by the packing of the side chains of aromatic amino acids around the Pro 2 residue in the case of the cis-isomers of EMs (Fig.…”
Section: Backbone Conformations and Secondarymentioning
confidence: 57%
“…These results indicated that the replacement of the C-terminal amide group by a carboxy group resulted in a higher flexibility for EM2OH. The subsequent structural examination of EM2 and its C-terminal free-acid analog carried out in different media (i.e., H 2 O, DMSO, TFE, and DPC micelles) by In et al [27] led to the similar observations regarding the backbone structure of the cisand trans-isomers of both tetrapeptides, as described in [29]. In this latter study, four different types of backbone conformation were distinguished, namely the rS-and n7-type open conformers, as well as the F1-and F2-type folded conformers, whose population ratios depended on the solvent type and pH.…”
Section: Backbone Conformations and Secondarymentioning
confidence: 81%
See 2 more Smart Citations
“…This may be related to the fact that amidation brings the C-terminal group to a neutral state, which in turn decreases the repulsion of carboxyl groups in the aspartic acid. This is known to play a key role in preventing the formation of a folded conformation for the C-terminal amidated peptide (46). An open conformation for OSN would allow more side chain interaction with calcium and phosphate ions (35).…”
Section: Discussionmentioning
confidence: 99%